Comparison of Two Aspergillus oryzae Genomes From Different Clades Reveals Independent Evolution of Alpha-Amylase Duplication, Variation in Secondary Metabolism Genes, and Differences in Primary Metabolism - Chacón-Vargas, Katherine; McCarthy, Colin O.; Choi, Dasol; Wang, Long; Yu, Jae-Hyuk; Gibbons, John G. (Frontiers in Microbiology, 2021)
Microbes (bacteria, yeasts, molds), in addition to plants and animals, were domesticated for their roles in food preservation, nutrition and flavor. Aspergillus oryzae is a domesticated filamentous fungal species traditionally used during fermentation of Asian foods and beverage such as sake, soy sauce, and miso. To date, little is known about the extent of genome and phenotypic variation of A. oryzae isolates from different clades. Here, we used long-read Oxford Nanopore and short-read Illumina sequencing to produce a highly accurate and contiguous genome assemble of A. oryzae 14160, an industrial strain from China. To understand the relationship of this isolate, we performed phylogenetic analysis with 90 A. oryzae isolates and 1 isolate of the A. oryzae progenitor, Aspergillus flavus. This analysis showed that A. oryzae 14160 is a member of clade A, in comparison to the RIB 40 type strain, which is a member of clade F. To explore genome variation between isolates from distinct A. oryzae clades, we compared the A. oryzae 14160 genome with the complete RIB 40 genome. Our results provide evidence of independent evolution of the alpha-amylase gene duplication, which is one of the major adaptive mutations resulting from domestication. Synteny analysis revealed that both genomes have three copies of the alpha-amylase gene, but only one copy on chromosome 2 was conserved. While the RIB 40 genome had additional copies of the alpha-amylase gene on chromosomes III, and V, 14160 had a second copy on chromosome II and an third copy on chromosome VI. Additionally, we identified hundreds of lineage specific genes, and putative high impact mutations in genes involved in secondary metabolism, including several of the core biosynthetic genes. Finally, to examine the functional effects of genome variation between strains, we measured amylase activity, proteolytic activity, and growth rate on several different substrates. RIB 40 produced significantly higher levels of amylase compared to 14160 when grown on rice and starch. Accordingly, RIB 40 grew faster on rice, while 14160 grew faster on soy. Taken together, our analyses reveal substantial genome and phenotypic variation within A. oryzae.